ISOLASI DAN PENENTUAN KADAR FLAVONOID EKSTRAK ETANOLIK HERBA SAMBILOTO (Andrographis paniculata (BURM.F.) NESS) - Ridwan Rais, Ichwan (Universitas Ahmad Dahlan, 2015)
(Andrographis paniculata ( Burm.f. ) Ness ) is containing andrografolid, neoandrografolid,and flavonoids known as apigenin-7,4â-di-O-methyl ether, 5-hydroxy7,8,2â,3âtetrametoxyflavon,dihydroxy-dimetoxyflavon. Flavonoids as antioxidants, have potential as an anti-bacterial activity,anti-inflammatory, anti-allergic and anti-thrombosis. The chemical structure of the drug may explainthe nature of the drug and linkage units and structures of drug molecules with biological activity.Compounds with the same functional groups can provide the same biological response due to work onthe same receptors. This present study is determine the total flavonoid content of the ethanol extract ofA. paniculata use Chang method, identification using spectrophotometric method. The measurementresults showed that total flavonoid content of the ethanol extract of A. paniculata amounted to 46.322g/kg.